Reframing Mathematics Learning in Philippine Public Schools: A Qualitative Analysis of Curriculum Reforms and Numeracy Policies - Jake Raymund F. Fabregar (International Journal of Research on Multidisciplinary Studies, 2026)
Mathematics education reforms shape what learners are expected to know and do, while also influencing how mathematics is taught and assessed in public schools. In the Philippines, recent reforms have responded to persistent learning gaps by placing greater emphasis on foundational competencies and numeracy. However, limited research has examined how these priorities are collectively reflected across curriculum, assessment, and learning recovery policies. This study addressed this gap through a qualitative analysis of publicly available Philippine education documents, examining how mathematics learning is framed across curriculum reforms and related policy initiatives. The documents reviewed included the K to 12 Mathematics Curriculum Guide, MATATAG Mathematics Curriculum Guide, assessment and learning recovery policies, the National Learning Camp, the National Learning Recovery Program, the Basic Education Development Plan 2030, and related mathematics education reports. The documents were analyzed thematically to identify recurring ideas, shifts in priorities, and connections among mathematical competencies, instructional expectations, and intended learner outcomes. The findings point to a shift from an emphasis on curriculum coverage and procedural skills toward foundational numeracy, conceptual understanding, mathematical reasoning, problem solving, and meaningful application. The documents also emphasize learner-centered, differentiated, inclusive, and assessment-informed instruction, together with teacher professional competence and targeted learner support. The study contributes an integrated policy-level view of these priorities by examining how they connect across multiple reforms rather than treating individual programs in isolation. The findings support continued efforts to strengthen curriculum coherence, teacher development, assessment, technology integration, and sustained learner support.